PENGARUH CITRA MEREK, KUALITAS PRODUK DAN INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN SIKAT GIGI CIPTADENT DI KOTA BATAM - Deviren Serena KHO; Inda Sukati (SCIENTIA JOURNAL, 2026)
The increasingly intense competition in the personal care product industry requires companies to better understand the factors influencing consumer purchase decisions. This study aims to analyze the effect of brand image, product quality, and product innovation on purchasing decisions of Ciptadent toothbrushes in Batam City. This research employs a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to consumers who use Ciptadent toothbrushes in Batam City, with the sampling technique using non-probability sampling. Data analysis was conducted using multiple linear regression analysis, supported by validity tests, reliability tests, and classical assumption tests. The results indicate that brand image, product quality, and product innovation partially have an effect on purchasing decisions. Furthermore, simultaneously, brand image, product quality, and product innovation have a significant influence on purchasing decisions of Ciptadent toothbrushes in Batam City.